The Relationship Between Metabolic Syndrome and Target Organ Damage in Ghanaian With Stage-2 Hypertension - Bello-Rodriguez, B M (Ghana Medical Association, 2013)
OBJECTIVES: To determine the frequency of Metabolic syndrome (MetS) in stage-2 hypertension and to assess the influence of MetS components over target organ damage (TOD) in Ghanaian patients. METHODS: Forty adult patients with stage-2 hypertension were enrolled in a cross-sectional study developed at the Police Hospital, Accra, between 1st February 2009 and 31st January 2010. Diagnosis of MetS was based on The National Cholesterol Education Program in Adult Treatment Panel Revised in 2005 criteria. The alterations on the heart, aortic and carotid arteries, retina, and kidneys were evaluated through the clinical examination including retinal funduscopy, chest X-Ray, ECG, and serum creatinine quantification. The Brain CT-scan was performed on the patients with clinical cerebrovascular disease manifestations. RESULTS: MetS was diagnosed in 25 cases (62.5%); female sex revealed significant association with MetS (OR, 4.88; 95% CI, 1.19–19.94; P=0.027). Ninety-five percent of patients had TOD. Coronary disease was associated with MetS (OR, 4.43; 95% CI, 1.026–19,27; P=0.047) and diabetes mellitus as single MetS component (OR, 14.00; 95% CI, 1.56–125.61; P=0.018). A positive significant correlation was shown of age with cerebrovascular disease (r=0.381; P=0.015) and coronary disease (r=0.623; P=0.000). Non-significant correlation or association (P>0.05) was shown between number of MetS components and number of TOD. CONCLUSIONS: In stage-2 hypertension patients a high frequency of MetS with a risk increase in female sex was observed. This stage hypertension is for itself an individual risk to develop cardiovascular disease with high frequency none related with MetS, although coronary disease risk was increased in diabetic patients.